Examining the effects of HIV self‐testing compared to standard HIV testing services: a systematic review and meta‐analysis - Johnson, Cheryl C; Kennedy, Caitlin; Fonner, Virginia; Siegfried, Nandi; Figueroa, Carmen; Dalal, Shona; Sands, Anita; Baggaley, Rachel (Journal of the International AIDS Society, 2017)
Introduction: HIV self‐testing (HIVST) is a discreet and convenient way to reach people with HIV who do not know their status, including many who may not otherwise test. To inform World Health Organization (WHO) guidance, we assessed the effect of HIVST on uptake and frequency of testing, as well as identification of HIV‐positive persons, linkage to care, social harm, and risk behaviour. Methods: We systematically searched for studies comparing HIVST to standard HIV testing until 1 June 2016. Meta‐analyses of studies reporting comparable outcomes were conducted using a random‐effects model for relative risks (RR) and 95% confidence intervals. The quality of evidence was evaluated using GRADE. Results: After screening 638 citations, we identified five randomized controlled trials (RCTs) comparing HIVST to standard HIV testing services among 4,145 total participants from four countries. All offered free oral‐fluid rapid tests for HIVST and were among men. Meta‐analysis of three RCTs showed HIVST doubled uptake of testing among men (RR = 2.12; 95% CI: 1.51, 2.98). Meta‐analysis of two RCTs among men who have sex with men showed frequency of testing nearly doubled (Rate ratio = 1.88; 95% CI: 1.17; 3.01), resulting in two more tests in a 12–15‐month period (Mean difference = 2.13; 95% CI: 1.59, 2.66). Meta‐analysis of two RCTs showed HIVST also doubled the likelihood of an HIV‐positive diagnosis (RR = 2.02; 95% CI: 0.37, 10.76, 5.32). Across all RCTs, there was no indication of harm attributable to HIVST and potential increases in risk‐taking behaviour appeared to be minimal. Conclusions: HIVST is associated with increased uptake and frequency of testing in RCTs. Such increases, particularly among those at risk who may not otherwise test, will likely identify more HIV‐positive individuals as compared to standard testing services alone. However, further research on how to support linkage to confirmatory testing, prevention, treatment and care services is needed. WHO now recommends HIVST as an additional HIV testing approach.